ERP in Public Sector Reform: A Systematic Literature Review of Technological, Organizational, and Institutional Factors - Ashar, Muhammad; Haliah, Haliah; Nirwana, Nirwana (Journal Research of Social Science, Economics, and Management, 2025)
Public sector reform has gained momentum worldwide, driven by the need for efficiency, accountability, and service improvement. Amid these efforts, the adoption of Enterprise Resource Planning (ERP) systems has emerged as a promising solution to modernize public sector operations. This study aims to provide a comprehensive understanding of the factors influencing ERP implementation in public sector reform through a Systematic Literature Review (SLR) of studies published from 2020 to 2024. The research examines three critical dimensions: technological, organizational, and institutional factors. Findings reveal that IT infrastructure readiness, system compatibility, and digital innovation are pivotal to the success of ERP systems, while organizational challenges such as bureaucratic structures and change resistance hinder effective implementation. Additionally, coercive, normative, and mimetic pressures from government policies and international standards drive ERP adoption. This research underscores the importance of a contextualized approach that integrates external pressures with internal readiness for digital transformation. The study contributes to ERP literature by offering a holistic view of public sector ERP challenges and opportunities and provides recommendations for policymakers to facilitate successful ERP adoption. Future research should explore cross-country comparisons and empirical case studies to further understand the nuanced implementation processes in different national contexts.